1999
DOI: 10.1002/(sici)1097-0010(199912)79:15<2105::aid-jsfa510>3.3.co;2-i
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of starches from West African yams

Abstract: Starches from four varieties of West African yams were extracted and characterised. The physicochemical properties investigated (granule size and morphology, amylose content, crystal form, gelatinisation and pasting behaviour) depended strongly on the yam variety. The starch granules extracted from water yam (Dioscorea alata), white yam (D rotundata) and yellow yam (D cayensis) varieties showed mononodal particle size distributions centred between 31 and 35 mm, while the bitter yam (D dumetorum) exhibited a bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
59
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(73 citation statements)
references
References 6 publications
13
59
1
Order By: Relevance
“…1). This observation was similar to those for D. alata (Farhat et al, 1999) and Japanese yam (Sugimoto et al, 1986), but different from elliptic and oval shapes of Dioscorea opposita Thunb var. Zhongbowen starch (Wang et al, 2007) and the oval shape of Discores nipponica Makino (Yuan et al, 2007).…”
Section: Resultssupporting
confidence: 84%
“…1). This observation was similar to those for D. alata (Farhat et al, 1999) and Japanese yam (Sugimoto et al, 1986), but different from elliptic and oval shapes of Dioscorea opposita Thunb var. Zhongbowen starch (Wang et al, 2007) and the oval shape of Discores nipponica Makino (Yuan et al, 2007).…”
Section: Resultssupporting
confidence: 84%
“…The DH of both Bola and Dik were higher than those reported for genotypes of sweet potato (12.9 J/g, Collado et al, 1999), potato (14.9 J/g, Ganga & Corke, 1999), taro (6.8 J/g, Jane et al, 1992), but lower than that reported for genotypes of yam (19.8 J/g, Farhat et al, 1999). The gelatinization characteristics of many other tuber starches have been determined by Kofler hot stage microscopy.…”
Section: Gelatinization Characteristicsmentioning
confidence: 53%
“…f o o d p a c k a g i n g a n d s h e l f l i f e 3 ( 2 0 1 5 ) 1 -8 conformations are disrupted by the formation of stable single chain V-conformation helices resulting in the glycerol-amylose complex (Farhat, Oguntona, & Neale, 1999;Manzocco, Nicoli, & Labuza, 2003;Zobel, 1994). As can be seen in Fig.…”
Section: 5mentioning
confidence: 99%